Understanding the Digital Work Behavior of Generation Z: The Impact of Internet Use and Price Perception on Satisfaction with ICON+ Services - Ridho Ferdiyansah, Muhammad; Pradana, Mahir; Sulistya S, Ariraya (JURNAL APARATUR, 2025)
Purpose– This study aims to examine the influence of internet consumption behavior and pricing on user satisfaction among Generation Z users of ICON+ internet services in Ciledug District, Indonesia. With Generation Z being digital natives and a key segment for internet service providers, understanding their preferences is crucial for sustaining competitiveness in a rapidly evolving digital market.Design/methods/approach– A quantitative research design was adopted using a structured questionnaire distributed to 100 Generation Z respondents selected via purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, and classical assumption tests were conducted using SPSS version 26 to ensure the robustness of the model.Findings– The results reveal that both internet access (β = 0.376, p < 0.001) and pricing (β = 0.341, p < 0.001) significantly and positively impact user interest and satisfaction toward ICON+ services. Internet access emerged as the stronger predictor. The model explains 50.9% of the variance in user satisfaction (R² = 0.509), suggesting a moderate to strong relationship.Research implications/limitations– The research is limited to a single district and service provider, which may affect the generalizability of the findings. It does not include other potential influencing variables such as user experience or brand trust.Originality/value–This study offers practical insights for internet service providers targeting Gen Z and contributes to the academic discourse on digital consumption behavior. It also serves as a foundation for future studies across broader geographic or demographic scopes.